2011
DOI: 10.1139/t11-076
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modeling of time-dependent stress–strain behaviour of saturated soils exhibiting both creep and swelling

Abstract: In general, clayey soils exhibit more or less both creep and swelling. In this paper, “creep” means viscous compression under a constant load condition in an oedometer test, while “swelling” means viscous expansion under a constant load condition in an oedometer test and is a reverse behaviour to creep for all saturated soils. Clayey soils containing the clay mineral montmorillonite show strong creep and swelling characteristics. Both creep and swelling characteristics have a significant influence on the defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…5 indicates that, with changing of the strain rate applied, the compression curve jumps from the current CRS curve to another one correspondingly. This observation was consistent with the results reported by Leroueil et al (1985), Watabe et al (2012) and Yin & Tong (2011) for saturated soils.…”
Section: Accepted Manuscriptsupporting
confidence: 94%
See 4 more Smart Citations
“…5 indicates that, with changing of the strain rate applied, the compression curve jumps from the current CRS curve to another one correspondingly. This observation was consistent with the results reported by Leroueil et al (1985), Watabe et al (2012) and Yin & Tong (2011) for saturated soils.…”
Section: Accepted Manuscriptsupporting
confidence: 94%
“…Based on multistage oedometer tests and CRS tests, Yin and Tong (2011) found that the bentonite-sand mixtures exhibit distinct nonlinear creep of swelling behavior, which demonstrates that time-dependent property of buffer/backfill material cannot be neglected.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations